Implementation of Label Cutting Workstations Improvement in The Jago Jaya Shuttlecock Industry to Increase Productivity Based on Ergonomic Aspects - Dwi Astuti, Rahmaniyah; Suhardi, Bambang; Iftadi, Irwan; Galda Nadhira, Afra; Syahliantina, Annisa (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2024)
Jago Jaya Shuttlecock Industry is an MSME in Jagalan, Surakarta, that produces shuttlecocks. Based on these conditions, a study was conducted in 2020 by Sherlinta Kaban, which produced a label cutting tool tested on a label cutting workstation. However, in the trial, there are several obstacles found in using the label cutting tool, so follow-up study to analyze and improve the label cutting tools in previous studies to produce a new design that can be re-implemented. Ergonomics aspects used in this study are analysis of work posture using REBA, measurement of standard time with Westinghouse adjustments, the study of left and right-hand map movements, and tool redesign using the Reverse Engineering method. The improvements include implementing a new label cutting tool that can improve the operator's work posture, reduce standard time, increase the number of standard outputs, and improve operator hand movements to increase productivity at label cutting work stations.